Gastric Infusion of Short-Chain Fatty Acids Improves Health via Enhance Liver and Intestinal Immune Response and Antioxidant Capacity in Goats - Shaima Mohmed Nasr Abdu; Ismail Mohamed Abdalla; Yongkang Zhen; Chong Zhang; Zanna Xi; Jianjun Ma; Yuhong Zhong; Jiaqi Lin; Rahmat Ali; Mengzhi Wang (Veterinary Sciences)
In the present study, we comprehensively investigated the impacts of the infusion of three short-chain fatty acids (SCFAs), sodium acetate (SA), propionate (SP), and butyrate (SB), to examine their respective roles in the gastrointestinal tract (GIT) health and innate immunity of twenty adult Guanzhong milk goats of 1.5 years of age. Infusion of SCFAs resulted in upregulating the activity of certain antioxidant enzymes in comparison with the control group. The SA group significantly (p < 0.05) increased the activity of the catalase (CAT) in the liver, glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) in the colon, and maleic dialdehyde (MDA) in the jejunum. SP significantly (p < 0.05) upregulated the activity of the total antioxidant capacity (T-AOC) in the ileum, CAT and MDA in the jejunum, CAT in the colon, and SOD in the liver. SB was significantly (p < 0.05) upregulated the activity of the T-AOC in the ileum, CAT in the jejunum, and T-AOC, CAT, SOD, and GSH-Px in the colon. Infusion of SCFAs resulted in significant (p < 0.05) increases in pro-inflammatory and anti-inflammatory cytokines in the intestine compared to the control group. We found that the SA group significantly (p < 0.05) upregulated the level of interleukin-1 beta (IL-1β) in the ileum and jejunum, as well as the levels of IL-6 and TNF-α in the colon, while the SP group significantly (p < 0.05) increased the level of IL-1β in the jejunum and the level of interleukin-10 (IL-10) in the colon. Furthermore, the SB group significantly (p < 0.05) upregulated levels of IL-1β in the jejunum, interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α) in the colon, and IL-10 in the cecum. Furthermore, some intestinal tight-junction proteins were significantly increased by SCFA infusion. SA significantly (p < 0.05) increased the claudin level in the ileum and occludin in the colon, while the SP group significantly (p < 0.05) upregulated the level of occludin in the jejunum and the claudin level in the ileum. Moreover, SB significantly (p < 0.05) increased the occludin level in the jejunum, claudin level in the ileum, and zonula occludens-1 (ZO-1) level in the colon and cecum. There are many positive associations among antioxidant, inflammatory cytokine, and tight-junction protein indexes in the liver and intestine. In conclusion, our results suggest that the gastric infusion of SA, SP, and SB might improve goat intestinal health through the positive influence on the antioxidant capacity, pro-inflammatory and anti-inflammatory cytokines, and tight-junction proteins.